Assessment of Ankle and Hindfoot Stability and Joint Pressures Using a Human Cadaveric Model of a Large Lateral Talar Process Excision. Issue 11 (March 2015) - Sands, Andrew; White, Charles; Blankstein, Michael; Zderic, Ivan; Wahl, Dieter; Ernst, Manuela; Windolf, Markus; Hagen, Jennifer E.; Richards, R. Geoff; Stoffel, Karl; Gueorguiev, Boyko; Agarwal., Suresh
<x xml:space="preserve">Abstract</x> Abstract Lateral talar process fragment excision may be followed by hindfoot instability and altered biomechanics. There is controversy regarding the ideal fragment size for internal fixation versus excision and a concern that excision of a large fragment may lead to significant instability. The aim of this study was to assess the effect of a simulated large lateral talar process excision on ankle and subtalar joint stability. A custom-made seesaw rig was designed to apply inversion/eversion stress loading on 7 fresh-frozen human cadaveric lower legs and investigate them in pre-excision, 5 cm3 and 10 cm3 lateral talar process fragment excision states. Anteroposterior radiographs were taken to assess ankle and subtalar joint tilt and calculate angular change from neutral hindfoot alignment to 10-kg forced inversion/eversion. Ankle joint pressures and contact areas were measured under 30-kg axial load in neutral hindfoot alignment. In comparison to the pre-excision state, no significantly different mediolateral angular change was observed in the subtalar joint after 5 and 10 cm3 lateral talar process fragment excision in inversion and eversion. With respect to the ankle joint, 10-cm3 fragment excision produced significantly bigger inversion tibiotalar tilt compared with the pre-excision state, P = .04. No significant change of the ankle joint pressure and contact area was detected after 5 and 10-cm3 excision in comparison with the pre-excison state. An excision of up to 10 cm3 of the lateral talar process does not cause a significant instability at the level of the subtalar joint but might be a destabilizing factor at the ankle joint under inversion stress. The latter could be related to extensive soft tissue dissection required for resection.